Mengkonstruksi Alternative Dispute Resolution (ADR) yang Berlandaskan Hukum Islam dalam Kerangka Hukum Nasional - Nita Triana (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2020)
ADR is an alternative dispute resolution, that consider peaceful and agreement. Such a dispute has been a long time known by Indonesia society. Musyawarah and mufakat principles that exist in Adat Law and Islah principle that exist in Islamic Law constitute Living Law in Indonesia. Principle of Law as forgiving, peaceful and agreement that exists in Islah can construct ADR in frame National Law system.